ANALYSIS OF TEACHER TALK IN ENGLISH CLASSES IN VOCATIONAL HIGH SCHOOL TELADAN MEDAN - Yuni Ansari Rambe (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The objective of this study at describing the types of Teacher Talk, the effectiveness/ineffectiveness of Teacher Talk, and the aspect of Teacher Talk in classroom observation. This study used descriptive qualitative method is employed in this study which tries to describe all phenomena that occurred in the classroom This study involved an English teacher as research subject in his class. The subject of this study has implemented English talk as a means of communication in learning process of his classroom. The subject here is a female teacher who has been teaching English for one years and graduated from the university of Medan.  This study was conducted in SMK Teladan located in Medan city. This study was done in twelfth grade.  This class consists of 22 students with 11 are males and 11 are females. The main data was taken through observation technique.  The data was collected by using recording and field notes. From analysis done, it was found that English teacher performed their interactional communicative features out of five in the classroom. The features are 1. Referential Questions 2. Content Feedback 3. Student initiated Talk. All communicative interactional features of teacher it happened in discussion activities, it could be concluded that the teacher performs their interactional communicative features in classroom interaction out of five. There  features  are: 1. Referential Questions 2. Content Feedback 3. Student initiated Talk.